THE ART OF PERSUASION: PATHETIC APPEAL VIS-À-VIS ETHICAL AND LOGICAL CONSIDERATIONS - Mutiti, Yakobo (Advances in Social Sciences Research Journal, 2019)
ABSTRACT Short story writing is a literary art whose creativity heavily depends upon the interplay between the writer and his influence upon the reader. There are four modes of discourse employed in creative writing: exposition, description, narration and persuasion. Exposition is concerned with the layout, style and organisation of events and the actors within them. It is the immediate revelation to the readers of the setting and other background information that is necessary for understanding the plot. Description employs the use of language terms in ‘graphical’ or picturesque representation of something or someone through detailed characterisation of colour, motion, sound, taste, smell and touch. Narration is the telling of a story in fiction, non-fiction, poetry or drama. Persuasion is a form of argumentation where the language employed is intended to convince, principally through appeals to reason or to emotion. This study is focalized on the mode of persuasion with the rhetorical and classical theories as the point of reference. The Greek philosopher Aristotle upheld the view that narration, whose essential purpose is to become persuasive, could only enjoy viability if it possessed the following appeals: ethos, logos, pathos and kairos. This study was a confirmation of Aristotle’s contention across first language and second language English readers; this was underscored by an annexed anthology within the study, depicting divergent fictional settings and all emanating from the same writer, to which reading subjects from these variegated contexts were exposed. Thereafter comprehensive questionnaire covering various dimensions of ethos, logos, pathos and kairos was used to elicit the reader responses in regard to their appreciation and understanding of story. The study is useful not only in cementing the classical tradition, but also as an indication that even in modern rhetoric, logos and kairos must be regarded as basic in any communication while ethos and pathos are mainly appellative, although of relative importance.